2018
DOI: 10.1101/251025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative analysis of synaptic pathology and neuroinflammation: an initial study in a female rhesus monkey model of the “synaptic” phase of Alzheimer’s disease

Abstract: Background: Soluble oligomers of the Aβ peptide (AβOs) are toxins that target and disrupt synapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our group recently showed that repeated intracerebroventricular injections of soluble oligomers of the Aβ peptide (AβO) triggers severe spine synapse loss and neuroinflammation, together with increased cerebrospinal fluid levels of Aβ 1‐42 and p‐tau in dlPFC and hippocampus of female rhesus monkeys. Hence, exogenous AβO administration could be fundamental to establishing a nonhuman primate model of early AD pathogenesis (Beckman et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently showed that repeated intracerebroventricular injections of soluble oligomers of the Aβ peptide (AβO) triggers severe spine synapse loss and neuroinflammation, together with increased cerebrospinal fluid levels of Aβ 1‐42 and p‐tau in dlPFC and hippocampus of female rhesus monkeys. Hence, exogenous AβO administration could be fundamental to establishing a nonhuman primate model of early AD pathogenesis (Beckman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, exogenous AβO administration could be fundamental to establishing a nonhuman primate model of early AD pathogenesis (Beckman et al, 2018).…”
Section: Synaptic Ps214-tau and Cognitive Statusmentioning
confidence: 99%
“…These changes to the brain are region specific. Previous studies have reported that the prefrontal cortex (PFC) is one the regions most affected by age, with significant decrease in synaptic density and cortical layer thickness [6,[15][16][17][18][19]. PFC plays an important role in working memory function, selfregulatory and goal-directed behaviors, all of which are vulnerable to aging [20].…”
Section: Introductionmentioning
confidence: 99%